INSTITUTIONS AND PUBLIC HEALTH IN CUBA IN THE FIRST HALF OF THE TWENTIETH CENTURY - Beldarraín Chaple, Enrique (2014)
This essay studies institutional development and the main facts of public health in Cuba in the beginning of the 20th century. It emphasizes some of those facts such as the general and environmental sanitation campaign that began in 1899 in an attempt to improve the population’s health with positive results. Another important fact is the development of the Cuban health care led by Dr. Carlos J. Finlay and the Escuela Cubana de Sanitaristas. In 1909 the Secretaría de Sanidad y Beneficiencia was created and multiples goals were achieved such as the eradication of yellow fever (1908), bubonic plague (1915), and smallpox (1923). In 1927 the Instituto Finlay was created. Patriotism was presented in this struggle to improve health in Cuba.